Looking for sharp edges: Modes of flint recycling at Middle Pleistocene Qesem Cave, Israel. (10th March 2015) - Parush, Yoni; Assaf, Ella; Slon, Viviane; Gopher, Avi; Barkai, Ran
Abstract: Qesem Cave is a Middle Pleistocene site in Israel assigned to the Acheulo-Yabrudian Cultural Complex (AYCC). The cave reveals a suite of innovative behaviors including intensive flint recycling activities. In this paper, we present a new classification system, developed for the study of lithic recycling at Qesem Cave. Through the careful technological analysis of hundreds of recycled items we have identified several recycling modes at Qesem Cave, including a specific production trajectory of blades and knives recycled from "old" flakes. We argue that the study of lithic recycling provides a significant glance at human decision-making processes and the technological repertoire of the late Lower Paleolithic, which are particularly pronounced when practiced within a lithic economy that enjoyed abundance rather than scarcity of stone. Our observations provide a more coherent view of AYCC lithic recycling which might be applied to the study of lithic recycling in other Paleolithic contexts.